Congenital Malformations In The West Of Iraq - AL-Janabi, Muhi K. (Journal of the Faculty of Medicine Baghdad, 2007)
Summary: Background: CM is the leading cause of infant deaths and account for much greater proportion of infant mortality’ than does premature birth. A malformation is a primary structural defect arising from a localized error in morphogenesis. This is a prospective study devoted to define the causes and frequencies of congenital malformations (CM) in Maternal and Children Hospital (MCH) in Al-Anbar govemorate (west of Iraq) and a comparison is done with other Iraqi and international studies. FdC Med Baghdad Methods: Congenital malformations were studied over a period of 2 years from the 1st of July 2000 2007/ Vol. 49, No.3 f0 fjle 30th ofJune 2002 in 12831 births including stillbirths at MCH in Al- Anbar govemorate (west Received July 2006 0f Iraq). A control group of 100 women who gave birth to normal newborn babies was studied Accepted Jan. 2007 similarly. Results: The overall birth prevalence of CM is 8.5/1000 births (109/1283 1) and stillbirth prevalence is 21/1000 (269/1283 1) births. The most common system involved in CM is the CNS that constitute 55% of total CM followed by skeletal system 33% then GIT 7% urogenital 2% recognized syndromes 2%, and others 1 %.This study shows a significant association between each of stillbirth, LBW, polhydraminious,parental consanguinity advanced maternal age and family history of CM.The present study shows no significant association with each of urban /rural status, and sex, attending antenatal care, tonics, fever, UTI, and diabetes mellitus. Conclusion: The overall birth prevalence of CM is almost the same as that recorded by Al-Saadoon et al in Basra which M’as 8.7/1000 in the year 1994 and lower than the birth prevalence of CM recorded by Grover-N in India in the year 2000 which M’as 17.8/1000 Associations between some of the risk factors and CM are similar and others are different from other studies.